(untitled) (Kronika Bydgoska, 2017)
The report of watchmaster Teodor Mory on activities of the 16th Greater Poland Uhlan Regiment describes actions of the regiment from the beginning of its reclaiming activities in Pomerania, in relation to fulfilment of the provisions of the Treaty of Versailles, until the end of the war against Bolshevik Russia in 1920, finished with signing of the Treaty of Riga. The first part is ready to be published. It contains description of activities of the 16th regiment, its second squadron, from the time of the mentioned beginning of reclaiming activities until the start of military actions in April 1920. The second part contains description of combat operations of the 16th regiment at the Polish-Soviet front. It is under preparation for publication.